Pengaruh Kompetensi SDM, Penerapan Sistem Akuntansi Desa, Dan Komitmen Pimpinan Terhadap Kualitas Laporan Keuangan Desa: Studi Empiris Kecamatan Ciawi - Suwarno, Suwarno; Lustrilanang, Pius; Sunardi, Sunardi (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
The purpose of the study was to determine the effect of human resource competence. Implementation of the village accounting system and leadership commitment to the quality of village financial reports. The object of research is a village located in the Ciawi sub-district, with a sampling technique using cluster sampling and 12 villages out of 13 were sampled in this study. Testing is done by using multiple regression analysis. The results of this study indicate that the competence of human resources. The implementation of the village accounting system and leadership commitment have a positive influence on the quality of village financial reports. Keyword : financial reports. human resource competence. accounting system. leadership commitment